FPGA accelerated radio galaxy classification with a Fourier convolutional neural network - Edwards, Barend Jacobus (Stellenbosch : Stellenbosch University, 2025)
Edwards, B. J. 2025. FPGA Accelerated Radio Galaxy Classification with a Fourier Convolutional Neural Network. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/0f7df7f9-5856-46d0-819c-c7f9bf4f8335